Miniaturization of optical sensors and their potential for high-throughput screening of foods - Rodriguez-Saona, Luis; Aykas, Didem Peren; Borba, Karla Rodrigues [UNESP]; Urtubia, Alejandra (Elsevier B.V., 2020)
Molecular fingerprinting technology has evolved from bulky laboratory benchtop instrumentation to field-deployable devices driven by advances in semiconductor and photonic technologies. The ongoing miniaturization of vibrational spectroscopy equipment has revolutionized the food industry by allowing on-site and real-time monitoring of food products and production processes to ensure quality and safety. The development of spectral libraries to fingerprint contaminants has provided unique detection capabilities to ensure consumer's product safety. Commercialization of handheld and ruggedized instrumentation for field deployment is enabling little or no sample preparation requirement, non-contact and non-destructive capabilities. Testing done as close to the original source would permit detecting risks before an ingredient has been diluted or combined with other ingredients. By producing a characteristic chemical 'fingerprint' with unique signature profiles, miniaturized molecular spectroscopy techniques combined with chemometric analysis have positioned as viable 'green' alternatives for field applications allowing phenotyping, quality assurance, authentication, and detection of adulteration and contaminants in foods. Contrary to NMR and mass spectrometry (MS) techniques, vibrational spectroscopy provides selectivity and specificity for screening raw materials without requiring costly instrumentation, labor-intensive and complex sample pretreatment, well-trained technicians to operate the instrumentation and are particularly amenable to be implemented for quality control in the field, manufacturing facilities, and grocery stores. In this review, enabling technologies for further miniaturization of vibrational spectroscopy equipment and their applications to the food industry are presented.